THE LATE RIPHEAN MIROEDIKHA MICROBIOTA FROM SIBERIA. PART 1: COMPOSITION AND FACIAL-ECOLOGICAL DISTRIBUTION OF ORGANIC-WALLED MICROFOSSILS - Veis A.F.; Petrov P.Yu.; Vorob'eva N.G. (My University, 1998)
The paper presents new data on taxonomic composition and formation environments of the Late Riphean Miroedikha microbiota from the Turukhansk Uplift, where it consists of organic-walled fossils and is most abundant and diverse as compared to biotas from other localities of the world. Microfossils formerly known from the lower subformation are now recovered from a greater part of the whole Miroedikha Formation. They are encountered at 10 levels of three sections studied at the Miroedikha, Enisei, and Bol'shaya Shorikha rivers. New data considerably extend information about the taxonomic diversity of biota. It includes 52 genera and 78 species of all morphological groups. In addition, nine and seven new morphotypes are established to be classifiable at the species and generic ranks, respectively. Lateral variations in biota composition are analyzed with respect to the transgressive and regressive trends of the Miroedikha basin evolution. The biota is divided for the first time into the shallow-water, transitional, medium-deep "optimal," and deep-water facial-ecological groupings. The established paleoecological localization of some important morphotypes (Chuaria, Trachyhystrichosphaera, Prolaroforma, Archaeoellipsoides, and others) was used to correct the formerly accepted standards of their distribution along the paleobasin profile. New data on lateral and vertical distribution of studied microorganisms support our earlier conclusion that their assemblages, displaying the most dynamic evolution and consisting of forms complex in the structure, were localized in the medium-deep part of the shelf, and that evolutionary innovations in the Riphean biota were mostly related to the regressive stages of sedimentary cycles.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей